Pengaruh Waktu Pemanasan Bayam Merah dan Bayam Hijau Terhadap Kadar Oksalat dengan Metode Spektrofotometri UV-Vis - Sheila Nabila Afri; Rahmadani Rahmadani; Mia Audina (CV. Wadah Publikasi Cendekia, 2023)
ABSTRACT. Spinach is a vegetable that is often consumed by Indonesian people with various preparations. Spinach has a high nutritional content, but spinach also has anti-nutrients, one of which is oxalate. How to cook spinach can affect the oxalate content in it. Too high oxalate content in spinach can interfere with kidney function. The purpose of this study was to see the effect of heating time for red spinach and green spinach on oxalate levels. This study uses an experimental type with a cross-sectional research design. The results of the quantitative analysis obtained were a decrease in oxalate levels in both red and green spinach. Oxalate levels in green spinach at minute 0 was 7.589 ppm, minute 3 was 7.234 ppm, minute 5 was 6.693 ppm, minute 8 was 6.255 ppm, minute 10 was 5.505 ppm. For red spinach, 0 minutes was 12.068 ppm, 3 minutes was 11.672 ppm, 5 minutes was 9.776 ppm, 8 minutes was 7.901 ppm, and 10 minutes was 6.464 ppm. Based on the results of the study, it can be concluded that heating with different time intervals (minutes) showed a significant effect on oxalate levels in red and green spinach, namely a decrease in oxalate levels.